Los códigos de vestimenta juvenil relacionados con reglamentos y presentación personal en los estudiantes de sexto año de Educación General Básica de la Unidad Educativa “Camilo Gallegos Toledo” del cantón Riobamba, provincia de Chimborazo, periodo académico 2020-2021. - Valencia Velarde, Jhoselyn Karolina (2022)
In this research work, dress codes arise as a problem when specific clothing rules might be followed, both in the educational institution and in certain events in the sixth-year EGB students of the "Camilo Gallegos Toledo" Educational Unit. The present study aims to determine the relationship between children's clothing and non-compliance with the school dress code. The theoretical framework entails essential aspects about the fashion that children follow, as well as criteria about dress codes that influence student clothing and the relationship with non-compliance with institutional dress codes. The methodology used is a mixed research approach with a nonexperimental design, by level or scope, descriptive, depending on the place, field, and bibliographic, the type of study, by time, the methods are Inductive, deductive analytical, and synthetic. The study populations were twenty-four people, twenty-three students, and one teacher. Two instruments were used for data collection: The student survey with eleven multiple-choice questions and an interview with the teacher with six open questions. With the data obtained, it was possible to establish that the children expressed that dress codes are interpreted as "being fashionable," This phrase is related to the economy, the influence of social networks, and the fanaticism of specific artists. On the other hand, non-compliance with the institutional dress code is due to ignorance of the rules and inadequate perspective regarding the code.